Political Movement and Electionlore: An Exploration of Iranian Politics Through Digital Folklore - Etaati, Saeedeh (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2018)
This paper is an ethnographic study of digital culture and Iranian online political humor: a hybridized genre of folklore which converges in both online and oral spheres where it is created and shared. It specifically explores the emergence and growth of politicized humorous cellphonelore, which I term “electionlore”, during and after the 2016 February elections in Iran. Analysing different joke sub-cycles in this electionlore, I argue that they serve as a powerful tool for my informants to construct their own “newslore” (Frank 2011) and make manifest what I define as “vernacular politics” through which they become mobilized and unified in their political activism. I diverge from the theory of “resistance jokes” (Powell and Paton 1988; Bryant 2006; Davies 2011) and propose a new framework for studying political jokes in countries suspended between democracy and dictatorship, demonstrating how jokes serve as an effective and strategic form of reform and unquiet protest.